2020
DOI: 10.1155/2020/5236045
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of Leptospirosis among High-Risk Individuals in Morocco

Abstract: Background. Leptospirosis is an anthropozoonotic reemerging neglected infectious disease underreported in most developing countries. A cross-sectional study was performed between 17 and 23 February 2014 to estimate the seroprevalence of leptospirosis among high-risk populations in Casablanca (Morocco). Methods. A total of 490 human serum samples (97.6% males) were collected in 3 high-risk occupational sites including the biggest meat slaughterhouse (n = 208), a poultry market (n = 121), and the fish market (n … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 29 publications
0
7
0
1
Order By: Relevance
“…We used as screening methods an ELISA against type IgM anti-Leptospira antibodies described by Kitashoji et al and following WHO guidelines [21,22]. Previous studies have suggested using this method for determining anti-Leptospira serum antibodies and for seroprevalence studies [23][24][25]. A set of serum of a hundred healthy control was used to validate the use of this protocol in DRC.…”
Section: Methodsmentioning
confidence: 99%
“…We used as screening methods an ELISA against type IgM anti-Leptospira antibodies described by Kitashoji et al and following WHO guidelines [21,22]. Previous studies have suggested using this method for determining anti-Leptospira serum antibodies and for seroprevalence studies [23][24][25]. A set of serum of a hundred healthy control was used to validate the use of this protocol in DRC.…”
Section: Methodsmentioning
confidence: 99%
“…They reported a probable recent leptospirosis seroprevalence of 1.9% associated with self-reported malaria within the past year 20 . Other studies reported varied leptospiral seroprevalence of 8.4% among febrile inpatients in North-Eastern Malaysia 21 , 24% among individuals in high-risk occupations in Morocco 22 , and 38.5% among miners in India 23 . Further, a study in Portugal revealed that 46% of the Sa˜o Miguel Island population has to circulate antileptospiral antibodies 24 .…”
Section: Resultsmentioning
confidence: 95%
“…Higher risk activities in the study from Western Uganda included skinning cattle and living close to monkeys 20 . Whereas most of the seropositive high-risk individuals in the study from Morocco 22 were involved in poultry (37%), market fish (26%), and meat slaughterhouse workers (15%).…”
Section: Resultsmentioning
confidence: 99%
“…They further reported a probable recent leptospirosis seroprevalence of 1.9% that was associated with having self-reported malaria within the past year [22]. Other studies reported varied leptospiral seroprevalence of 8.4% among febrile inpatients in North-Eastern Malaysia [23], 24% among individuals at high-risk occupations in Morocco [24] and 38.5% among miners in India [25]. Further, a study in Portugal revealed 46% of Sa˜o Miguel Island population has circulating anti-leptospiral antibodies [26].…”
Section: Discussionmentioning
confidence: 95%
“…Considering the fact that people living in these areas rely on the mentioned natural water sources without prior treatment suggest another possible risk for acquiring the infection. Higher risk activities in the study from Western Uganda included skinning cattle and living in close proximity to monkeys [22] whereas most of the seropositive high-risk individuals in the study from Morocco [24] were involved in poultry (37%), market sh (26%) and meat slaughterhouse workers (15%).…”
Section: Discussionmentioning
confidence: 99%